Care and control: an ethical analysis of parenting support within a UK prison mother and baby unit - Mortimer, R (2019)
This research is an empirical ethics study of parenting support delivered within a UK prison mother and baby unit (MBU). In recent years, the idea of state provided ‘parenting support’ has gained prominence within the early intervention (EI) policy agenda. A central claim of EI policy is that poor parenting during the early years of life can lead to a range of bad outcomes for children, such as ill health, academic failure, poverty, and crime. These outcomes create substantial costs for both individuals and society. Therefore, EI often involves identifying babies and children who are at risk of being ‘poorly parented,’ and intervening upon these parents in order to help them provide better care to their children. In the context of EI, parenting support gives rise to a number of complex ethical questions, both in policy and in practice. These concern what it means to be a good mother, the nature of a good childhood, the rights and responsibilities of parents, and the appropriate role of the state to intervene in family life. Prison MBUs provide an informative and challenging case study through which to consider how these ethical questions arise in practice for those involved in the delivery and receipt of parenting support. In the UK, female prisoners who are pregnant or who have a small child are able to apply to serve their sentence within a prison MBU. The baby can remain within the unit up until the age of 18 months, and whilst the mother serves her sentence she is provided with various kinds of parenting support. Some of these forms of parenting support look very similar to that which is provided to women enrolled in EI programs in the community. However, prison policy is unclear as to the goals of parenting support in this environment and it is possible to anticipate a number of ethical challenges that may arise in practice: how can prison provide a good start in life for children? What is the relationship – if any – between crime and being a good mother? To what extent can and should women exercise parental autonomy in a prison environment? Over a period of 7 months I conducted interviews, focus groups, and participant observation within the MBU of a women’s prison in the North of England. In this thesis I provide a rich ethical analysis of the practice of parenting support as it take place within the ‘moral world’ of the MBU. I elucidate the relevant ethical questions arising in this context, map out the values and normative commitments in play, identify where lack of clarity impedes the pursuit of goals, and analyse these concerns within a framework informed by relevant ethical theories. I situate these findings in the context of the EI policy literature in order to consider what this case study reveals about the ethical dimensions of parenting support both in prison and in EI policy more broadly. With this in mind, I offer some recommendations that may shape the provision of parenting support both inside and outside of prison.